2021
DOI: 10.1101/2021.10.29.466491
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondria-containing Extracellular Vesicles (EV) Reduce Mouse Brain Infarct Sizes and EV/HSP27 Protect Ischemic Brain Endothelial Cultures

Abstract: Ischemic stroke causes brain endothelial cell death and damages tight junction integrity of the blood-brain barrier (BBB). We engineered endothelial cell-derived extracellular vesicles (EVs) for the delivery of exogenous heat shock protein 27 (HSP27) and harnessed the innate EV mitochondrial load as a one, two-punch strategy to increase brain endothelial cell survival (via mitochondrial delivery) and preserve their tight junction integrity (via HSP27 delivery). We demonstrated that endothelial microvesicles bu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 141 publications
0
9
0
Order By: Relevance
“…Free ATP has a very short half-life (∼10 minutes). Here, we have formulated ATP-LNPs for ATP uptake by the BECs, whose protection is of central importance in conditions like stroke (14, 66, 67). Our prior works have shown that transfer of mitochondria to hypoxic BECs increased their relative ATP levels and concomitantly, their cell viability (14, 67).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free ATP has a very short half-life (∼10 minutes). Here, we have formulated ATP-LNPs for ATP uptake by the BECs, whose protection is of central importance in conditions like stroke (14, 66, 67). Our prior works have shown that transfer of mitochondria to hypoxic BECs increased their relative ATP levels and concomitantly, their cell viability (14, 67).…”
Section: Discussionmentioning
confidence: 99%
“…For studies using cells maintained under normoxic conditions, they were supplemented with the complete growth medium and maintained in a humidified incubator at 37 ºC and 5% CO 2 . For studies under hypoxic conditions, cells were supplemented with the oxygen-glucose deprived (OGD) medium (14) and were maintained in a Billups-Rothenberg chamber pre-flushed with 5% carbon dioxide, 5% hydrogen and 90% nitrogen at maintained at 37 ± 0.5 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Both large (m/lEVs) and small (sEVs) EV fractions are collectively referred to as EVs wherever applicable. We used a differential ultracentrifugation method to isolate m/lEVs and sEVs from the EV-conditioned supernatants of BECs and macrophages [11,14,26,27]…”
Section: Isolation Of Sevs and M/levsmentioning
confidence: 99%
“…EVs retain membrane signatures (lipids and proteins) reminiscent of their donor/parent cells that may allow increased uptake into recipient cells of the same type [9,10]. Our laboratory has previously demonstrated that m/lEVs derived from brain endothelial cells (BECs) increase mitochondrial function in the recipient BECs and also result in reduced brain tissue infarct volumes in a mouse model of transient ischemic stroke [11][12][13][14]. We have demonstrated that BEC-derived EVs (BEC-EVs) show a greater extent of fluorescent mitochondria signals in the recipient BECs as opposed to EVs derived from a macrophage cell line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation